PENINGKATAN HASIL BELAJAR IPA SISWA KELAS VI MELALUI MEDIA PEMBELAJARAN VIDEO PADA TEMA 6 DAN 7 TOPIK BIOLOGI - Enin Iriani (Program Studi Pendidikan Biologi, Fakultas Pendidikan Ilmu Eksakta dan Keolahragaan, IKIP Budi Utomo Malang, 2019)
Integrated or thematic learning of science at the school level must continue to be improved. The purpose of this study was to improve the learning outcomes of science students in themes 6 and 7 on the topic of Biology through the use of video. The research method used in this study was classroom action research with 2 cycles. This research was conducted in January-February 2019 at State Elementary School 02 Jatimulya (SDN Jatimulya 02), Bekasi. The number of samples used was 36 students. Science learning outcomes of Biology topics after being given a learning video experienced an increase, although not large, while a gain score of 0.14 with a low gain score criteria. In conclusion, there was an increase in science learning outcomes on the topic of Biology after being given a learning video.